1992
DOI: 10.1111/j.1748-5827.1992.tb01030.x
|View full text |Cite
|
Sign up to set email alerts
|

Tremor syndromes in dogs: Diagnosis and treatment

Abstract: Tremor is frequently associated with a variety of diseases in human beings and animals. Unlike humans beings, however, many tremor disorders of animals resist strict classification and have poorly defined aetiologies. In dogs, generalised tremor is more commonly recognised than tremor localised to one body area. History and clinical presentation remain important in the differential diagnosis of these disorders. Appropriate therapy for several of these syndromes can result in long term control or resolution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 15 publications
1
13
0
2
Order By: Relevance
“…161 Similar movements were reported in a Shetland sheepdog. A coarse tremor, often called a "head bob," has been described in the Doberman pinscher, boxer, and English bulldog.…”
Section: Orthostatic Postural Myoclonus In Great Danessupporting
confidence: 69%
“…161 Similar movements were reported in a Shetland sheepdog. A coarse tremor, often called a "head bob," has been described in the Doberman pinscher, boxer, and English bulldog.…”
Section: Orthostatic Postural Myoclonus In Great Danessupporting
confidence: 69%
“…None of the included patients received antiepileptic medication. Although no drug studies have been published, it has been suggested that these treatments do not alter the clinical course of EBs with IHT . It seems unlikely that IHT in EBs represents a seizure disorder.…”
Section: Discussionmentioning
confidence: 99%
“…47,48 As affected dogs get older, a progressive tremor of the pelvic limbs may begin and progress to involve the thoracic limbs. These animals never display weakness and have normal neurologic examinations, and tremors are accentuated during the excite- ment that accompanies physical examination.…”
Section: Tremorsmentioning
confidence: 99%